Quantitative Global Estimates for Generalized Double Szasz-Mirakjan Operators - Mehmet Ali Özarslan; Hüseyin Aktuğlu (Journal of Applied Mathematics)
We introduce the generalized double Szász-Mirakjan operators in this paper. We obtain several quantitative estimates for these operators. These estimates help us to determine some function classes (including some Lipschitz-type spaces) which provide uniform convergence on the whole domain .